Implementing National English Curriculum at Elementary Level - Muhammad Juliansyah Bedrio D; Tharisa Aura Maharani; Diba Yuri Mustafa; Leil Badrah Zaki; Hilarius Raditya Priambada Purba (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research examines the educational programs at an elementary school in Batam City, Indonesia, incorporating both the national and Cambridge curricula. The goal is to identify key elements that improve the quality and efficiency of education. Data was gathered through observations, interviews with three English teachers, and documentation using a qualitative case study method. The study utilized an observation checklist and interviews modified from earlier research. The results show nine key components essential for successful teaching and learning: engagement, interaction, motivation and goals, diversity of approaches, professionalism and support, teamwork, organization and response, group projects and communication, and flexibility. Various methods were found to improve the quality of learning through engagement. Dynamic exchanges in interactivity enhanced participation and promoted ongoing improvement. Student engagement was fueled by motivation and clear objectives, as various teaching techniques accommodated different learning preferences. Professionalism, combined with guidance, involved a mix of firmness and empathy to assist students with their academic and emotional needs. Teamwork between educators and stakeholders enhanced teaching techniques. Effective planning and constructive feedback led to optimal learning outcomes. Collaborative tasks encouraged the development of teamwork and problem-solving abilities within groups. Ultimately, teachers were able to effectively address curriculum changes and student needs due to their adaptability. To sum up, the research highlights how integrating these factors is crucial in establishing a vibrant and supportive learning atmosphere, necessary for students to thrive in a globalized academic setting.